Methodology for a local road safety plan : – non-motorized modes (plsv-mnm): case of Medellín - Gómez, Juan Manuel; Serna, Sandra Milena (Ingeniería Solidaria, 2014)
According to accident figures recorded between 2006 and 2012 in the city of Medellín, more than half of those killed in traffic accidents are bicyclists and pedestrians. That is why local authorities have the duty to develop and implement a road safety plan, coherent with the National Road Safety plan (Plan Nacional de Seguridad Vial, pnsv 2001-2016), established by the Government of Colombia through its Ministry of Transport, with the aim of reducing deaths from traffic incidents by 50%. A methodology is therefore proposed to diagnose, plan and evaluate necessary interventions to reduce the mortality of the most vulnerable actors on the roads.